Editors, artists and the changing status of manga in Japanese society, 1986-1995 - Kinsella, S (1996)
The contemporary Japanese manga industry began in 1959 when the first weekly manga magazines were published. Throughout the 1960s publishing companies attracted a large adult readership by incorporating radical political themes and realistic drawing styles in manga magazines. The readership continued to expand throughout the 1970s and 1980s and manga became a mass medium on a similar scale to television or pop-music. This thesis identifies two distinct trends in the cultural status of manga which were developing from the mid-1980s onwards. On the one hand, what had previously been seen as 'commercial' manga became respected as an 'art' form and highbrow communication medium. On the other, manga was vilified as pornography and as the extreme expression of an increasingly fragmented society. In the former trend, prestigious corporations sponsored a new category of 'information' manga, whilst in the latter, 'girls' and 'otaku' manga genres were censured by a quasi-governmental censorship movement. The amateur manga subculture in particular became the focus of a 'moral panic' where those involved were characterised as isolated and socially dysfunctional. This thesis, based on ten months' participant observation and intensive interviews in 'Morning' manga magazine editorial office in 1994, examines how this editorial was influenced by the changing status of manga in Japanese society in the formulation of its editorial policy and production methods. Editors felt that in the 1990s social changes presented the manga industry with serious production problems - in particular, a dearth of 'good' artists who could produce social themes, and a shrinking readership. Morning editorial attempted to overcome these problems by pioneering a new form of artistic, high-quality and respectable adult manga, aimed at older and more socially-elite readers. By creating a new proactive intellectual role for manga editors at the same time as sponsoring experimental graphic styles, Morning editorial produced a distinctive new form of conservative, state-supporting social and political adult manga. The re-definition of specific genres of manga as 'art' by Japanese institutions was paralleled by changes in commercial manga production which privileged the social and intellectual interests of editors over those of readers and artists. This study concludes that editors have become increasingly impo7tant in manga production between 1986 and 1995, and that there is a tight interrelationship between commercial cultural production and broader cultural and social discourses generally.